Analysis and sampling of atmospheric particles of precipitation sub-events in Istanbul, Turkey - AKKOYUNLU, BÜLENT OKTAY (My University, 2022)
The scavenging of atmospheric particles from the atmosphere is known to be efficiently carried out by the below-cloud scavenging process. To examine this process, a total of 51 sub-event samplings was carried out in 10 precipitations during a 129-day sampling period. PM2.5 samples were also collected simultaneously. The concentrations of Na, Mg, K, Ca, Al, Cu, Mn, and Fe were determined in the sub-events as well as in PM2.5 samples, and the pH values were also measured. The observed volumeweighted mean pH values of the precipitation sub-events were between 6.58 and 8.32, with an average value of 7.28. It was observed that the element with the highest average volumeweighted mean concentration value in precipitation was Na. Among the elements in PM2.5 particles, K had the highest concentration value. Next, the scavenging ratios of the elements were calculated in the precipitations that occurred. According to the averages of scavenging ratios of precipitations, it was determined that the element with the highest scavenging ratio was Na and the element with the lowest scavenging ratio was Fe. In addition, scavenging indexes were also determined in precipitations events. Variations in the scavenging properties of the elements were observed in each sub-event. The novelty of this study is that it is the first study carried out in Istanbul and even Turkey in terms of calculating scavenging indexes in sub-event sampling. Although this study is local, however, the importance of studies like this should not be ignored in terms of testing different air quality models.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Aquatic Science; Nature and Landscape Conservation; Environmental Science (miscellaneous); Physical Sciences; Life Sciences; PM2; 5; Rainwater; Scavenging index; Scavenging ratio; Sub-event; WET DEPOSITION; CHEMICAL-COMPOSITION; PARTICULATE MATTER; SCAVENGING RATIOS; AEROSOL; VARIABILITY; RAINFALL; ELEMENTS; URBAN; AREA; PM2.5